(untitled) (Research, Society and Development, 2021)
The objective of the study was to evaluate the performance of a local drip irrigation system in the cultivation of the passion fruit tree, determined the efficiency of water application through mathematical and probabilistic models. The study was conducted at Fazenda Areião, an experimental area of ESALQ/USP, Piracicaba/SP. The evaluation of the efficiency of the irrigation system based on the water volume distribution data obtained from the field tests was based on the following performance parameters: water application efficiency (Ea), storage efficiency (Es), deep percolation (Pp), percentage deficit (Gd) and degree of irrigation adequacy (Gad). For the evaluation of these parameters and the efficiency of the irrigation system, three different methodologies were used based on mathematical and statistical modeling procedures: the first methodology is based on mathematical expressions according to the Standard Mathematical Model (MMP), the second and third methodologies proposed by this study are based on the statistical procedure using the Nonlinear Regression Model (MRLN) and the Nonlinear Probabilistic Model (MPNL). The results showed that no differences were observed between the three models proposed as indicative of measures of efficiency of irrigation water application, also concluding that the irrigation system under study is in perfect operating conditions. However, the best results of average storage efficiency were obtained by means of the statistical model of third-degree polynomial adjustment, with a value of 99.88%.